1985
DOI: 10.1111/j.1532-5415.1985.tb07109.x
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Cognitive Impairment in the Elderly

Abstract: In order to determine the meaning of cognitive impairment in community dwelling elderly, 3,481 adults were interviewed in their homes using the Mini-Mental State Examination. Ninety-six per cent of the population aged 18-64 scored 23 or higher, whereas 80 per cent of the population 65 and over scored 23 or higher. Individuals with low scores were suffering from a variety of psychiatric disorders including dementia. Thirty-three per cent of the elderly population scoring in the range of 0-23 had no diagnosable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
288
1
11

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(306 citation statements)
references
References 6 publications
6
288
1
11
Order By: Relevance
“…This non-equivalence is at least in part due to the historical effects of school segregation in the US prior to 1954, and associated factors like lower education expenditures, shorter school years, and higher student/teacher ratios that were experienced by African American students (Loewenstein, Arguelles, Arguelles, & Linn-Fuentes, 1994;Whitfield & Wiggins, 2003;. Investigators have suggested future research should explore the role of education, both quantitatively and qualitatively, in the epidemiology of cognitive impairment associated with Alzheimer's disease (e.g., Folstein, Anthony, & Parhad, 1985;Whitfield, 2002;Whitfield & Wiggins, 2003). Furthermore, Whitfield (1996Whitfield ( , 2002 suggested that studies should examine the practical aspects of cognitive functioning, including performance on measures of everyday problem solving, in the assessment of cognitive status.…”
Section: The Role Of Education In Cognitive Performancementioning
confidence: 99%
“…This non-equivalence is at least in part due to the historical effects of school segregation in the US prior to 1954, and associated factors like lower education expenditures, shorter school years, and higher student/teacher ratios that were experienced by African American students (Loewenstein, Arguelles, Arguelles, & Linn-Fuentes, 1994;Whitfield & Wiggins, 2003;. Investigators have suggested future research should explore the role of education, both quantitatively and qualitatively, in the epidemiology of cognitive impairment associated with Alzheimer's disease (e.g., Folstein, Anthony, & Parhad, 1985;Whitfield, 2002;Whitfield & Wiggins, 2003). Furthermore, Whitfield (1996Whitfield ( , 2002 suggested that studies should examine the practical aspects of cognitive functioning, including performance on measures of everyday problem solving, in the assessment of cognitive status.…”
Section: The Role Of Education In Cognitive Performancementioning
confidence: 99%
“…The Mini-Mental State Examination (MMSE) (Folstein et al, 1985) and Mattis Dementia Rating Scale (Mattis, 1976) were administered to evaluate cognitive status. Patients and controls had routine physical examinations and blood tests (including thyroid hormone levels).…”
Section: Subject Selectionmentioning
confidence: 99%
“…The mean age of the LTCI residents was 82.3 years (60-97 years), and the population was predominantly female (n = 21; 52.5%) and Caucasian (n = 34; 85.0%). All elderly were classified as having some kind of dependency and cognitive impairment observed through the scores of Barthel index (with average of 40) and Mini Mental State Examination (average of 20) respectively. This strategy (dependent and cognitive impairment elders) was used to guarantee that only the caregiver participation in the hygiene process was known, considering that the diet also has not changed during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria were: the elder should consent in participate, have a minimum age of 60 years, be classified as partially functional dependent by Barthel index 19 , as well as have impairment according to Mini Mental State Examination score 20 .…”
Section: Study Population and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation